2012
DOI: 10.1111/j.1360-0443.2012.03793.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐level analysis of alcohol‐related injury and drinking pattern: emergency department data from 19 countries*

Abstract: Aim While drinking in the event is an important factor in injury occurrence, pattern of usual drinking may also be important in risk of injury. Explored here is the relationship of an alcohol-related injury with individual usual drinking pattern. Design Alcohol-related injury is examined using Hierarchical Linear models, taking into account individual usual volume of consumption over the past 12 months, as well as aggregate-level detrimental drinking pattern (DDP) and alcohol policy measures. Setting Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 11 publications
5
46
0
2
Order By: Relevance
“…18 However, the data are very sparse and most studies are based on case analysis or small clinical samples. This points to the need for better epidemiological surveillance of alcohol use indicators in China's general population.…”
Section: Alcohol-related Harmmentioning
confidence: 99%
“…18 However, the data are very sparse and most studies are based on case analysis or small clinical samples. This points to the need for better epidemiological surveillance of alcohol use indicators in China's general population.…”
Section: Alcohol-related Harmmentioning
confidence: 99%
“…Alcohol intoxication is well documented to increase the prevalence of trauma. Approximately 25% of injuries treated in emergency departments are alcohol related (Cherpitel et al, 2012). However, elucidating the impact of alcohol on clinical outcomes from traumatic injury is difficult to determine because of variables such as prior health status, genetics, and severity of injury, all of which can be controlled in the laboratory setting.…”
mentioning
confidence: 98%
“…A case-control study in Australia, however, found that after adjusting for the main effect of acute alcohol intake on injury among ED patients, regular alcohol intake, even at high usual daily levels, carried lower risks of injury than abstinence (Watt et al, 2004). Multilevel analysis of ARI in ED data from a large number of studies and countries found that although volume of alcohol was a signifi cant predictor (Cherpitel et al, , 2012, drinking pattern also predicted an ARI (with volume controlled for), with episodic heavy and frequent heavy drinking both more predictive of ARI than other drinking patterns (Cherpitel et al, 2012).…”
mentioning
confidence: 99%